2018
DOI: 10.1371/journal.pone.0209272
|View full text |Cite
|
Sign up to set email alerts
|

Use of C-reactive protein for the early prediction of anastomotic leak after esophagectomy: Systematic review and Bayesian meta-analysis

Abstract: BackgroundEarly suspicion, diagnosis, and timely treatment of anastomotic leak after esophagectomy is essential. Retrospective studies have investigated the role of C-reactive protein (CRP) as early marker of anastomotic leakage. The aim of this systematic review and meta-analysis was to evaluate the predictive value of CRP after esophageal resection.MethodsA literature search was conducted to identify all reports including serial postoperative CRP measurements to predict anastomotic leakage after elective ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…We congratulate the authors for the idea to investigate the postoperative CRP predictive value in the diagnosis of ICs after mesh-reinforced ventral hernioplasty. This paper strengthens and broadens this concept previously investigated in other general surgery settings [2][3][4]. After carefully reading, CRP seems to be a useful biomarker to rule out postoperative ICs.…”
Section: Dear Editorsupporting
confidence: 77%
“…We congratulate the authors for the idea to investigate the postoperative CRP predictive value in the diagnosis of ICs after mesh-reinforced ventral hernioplasty. This paper strengthens and broadens this concept previously investigated in other general surgery settings [2][3][4]. After carefully reading, CRP seems to be a useful biomarker to rule out postoperative ICs.…”
Section: Dear Editorsupporting
confidence: 77%
“…Similar to CRP, the accuracy of leucocytes as a biomarker for AL lies in excluding rather than indicating this postoperative complication [36,37,74]. Similar conclusions were drawn by a recently published systematic review and meta-analysis by Aolfi and colleagues, who also concluded that CRP may be a useful marker to rule out leakage with reassuring clinical and radiological signs [77].…”
Section: Discussionmentioning
confidence: 73%
“…It may be important to recognize that the current recommendation of enhanced recovery programmes specifically suggests ‘solid’ food to be provided to patients after surgery. Therefore, it may be time to consider the consumption of customary unprocessed foodstuffs beyond their effect on BMI, serum protein markers and other standard nutritional parameters.…”
Section: Discussionmentioning
confidence: 99%